Finding the peaceful coexistence of wildlife and salt licksusing machine learning for Royal Belum Rainforest conservation / Mimi Sophia Sarbandi ... [et al.] - Sarbandi, Mimi Sophia; Alias, Ahmad Nazib; Daud, Dzulsuhaimi; Mohamed Zabidi, Zubainun (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Royal Belum Rainforest was gazetted as the Royal Belum State Park on 3 May 2007 and is operated by Perak State Park Corporation. Located in the Perak state of Peninsular Malaysia, the Royal Belum Rainforest with an area of 117,500 ha, is part of the even bigger Belum-Temenggor Forest Complex. Geographically, about 57% of the Royal Belum Rainforest is in the range of 80-300m above sea level, and another 41% in the range of 300-1500 m above sea level. Dating back over 130 million years, the Royal Belum Rainforest is one of the world’s oldest rainforests, older than the Amazon Rainforest (South America) and Congo Rainforest (Africa). Within the Royal Belum Rainforest, lies Lake Temenggor, the second largest man-made freshwater lake in Peninsular Malaysia, covering 15,200 ha with hundreds of islands.